The Historical Geography of Betä Ǝsraʾel (Ethiopian Jewish) Involvement in the Conflict between the Solomonic Kingdom and the Forces of Imām Aḥmad b. Ibrāhīm al-Ġāzī - Kribus, Bar (Aethiopica, 2024)
The Səmen Mountains, the core region of Betä Ǝsraʾel political autonomy (fourteenth–seventeenth century), played a key role in the sixteenth-century conflict between the Solomonic Kingdom and the forces of Imām Aḥmad b. Ibrāhīm al-Ġāzī. While the involvement of the autonomous Betä Ǝsraʾel in this conflict has been addressed in scholarship, the sites associated with this involvement had not been accurately pinpointed. In 1959, Charles Fraser Beckingham published an article, in which he traced geographical aspects of the campaigns of 1542 waged as part of the above-mentioned conflict. A key site which he addressed was the ‘Mountain of the Jews’. This stronghold played a key role in these campaigns, and within it, the Solomonic monarchy found a safe haven and a base from which to launch the war to re-take the northern Ethiopian Highlands. Beckingham correctly suggested a general location for this stronghold but was unable to locate it with precision due to lack of detailed geographical information on the eastern Səmen Mountains. Based on a detailed examination of historical and modern maps, satellite images, and information posted on social media, this study suggests an exact location for this stronghold and other sites mentioned in the context of Betä Ǝsraʾel involvement in the conflict in question. This enables this involvement to be re-evaluated and better understood in light of the precise geographical context of the events in question.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" /><br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />